2010
DOI: 10.1039/b922596j
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear dynamical effects on reaction rates in thermally fluctuating environments

Abstract: An analytical framework to scrutinize the physical origin, especially nonlinear dynamical effects, of rate constants in thermal fluctuation is developed.A framework to calculate the rate constants of condensed phase chemical reactions of manybody systems is presented without relying on the concept of transition state. The theory is based on a framework we developed recently adopting multidimensional underdamped Langevin equation in the region of rank-one saddle. The theory provides a reaction coordinate expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 70 publications
0
19
0
Order By: Relevance
“…The other stimulating subject is the combination of the present theory and the recently developed dynamical reaction theory to extract the rigorous reaction coordinate to dominate the fate of reactions under thermal fluctuation in equilibrium. [6][7][8][9][10][11][12][13][14][15][16][17] These should provide us with great new insights into many molecular events occurring in nonstationary environments.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The other stimulating subject is the combination of the present theory and the recently developed dynamical reaction theory to extract the rigorous reaction coordinate to dominate the fate of reactions under thermal fluctuation in equilibrium. [6][7][8][9][10][11][12][13][14][15][16][17] These should provide us with great new insights into many molecular events occurring in nonstationary environments.…”
Section: Discussionmentioning
confidence: 99%
“…3 An example of such statistical property of the random force is the fluctuation-dissipation theorem, where the autocorrelation function of the random force is related to the friction kernel. It was found recently [6][7][8][9][10][11][12][13][14][15][16][17] that even though one cannot know an instantaneous value of the random force in advance since the initial condition of the bath is unknown, the statistical property enables us to analytically derive the boundary of the reaction in the state space, that is, a surface on which the system should end up with the reactant and the product with equal probability of one half. Following the pioneering works by Kramers 1 and by Grote and Hynes, 2 great progress [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] in the study of reaction dynamics in condensed phase have been made by using the GLE or the Langevin equation (a memoryless limit of GLE).…”
Section: Introductionmentioning
confidence: 99%
“…The potential of the theories has been demonstrated not only in chemical reactions with 17,22 and without [23][24][25][26][27] time-dependent external field but also in ionization of a hydrogen atom in crossed electric and magnetic fields, [28][29][30] isomerization of clusters, [31][32][33][34][35][36] and the escape of asteroids from Mars 37,38 [Just recently the theory was also generalized to quantum Hamiltonian systems [39][40][41] and dissipative (generalized) Langevin systems. [42][43][44][45][46][47][48][49][50][51] The dimension of the phase space of an N -particle nonrigid system is (6N − 10) in the upper limit. 52 Nonrigid molecules at constant energy have ten constraints of the three coordinates of center of mass, the three conjugate momenta of center of mass, the three angular momenta (defined in the space-fixed frame), and the total energy of the system.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, in order to extract the reaction coordinate and the no-return transition state for nonlinearly coupled multimode systems in a fluctuating environment, we have presented a theory [11][12][13][14] based on the concept of normal form 15 with the time-dependent formulation 16 within the framework of the multidimensional Langevin formulation. It was shown that, under certain conditions, a nonlinear coordinate transformation can be performed to provide a new reaction coordinate independent of all the other coordinates similarly to the case of Hamiltonian systems in the region of saddles.…”
Section: Introductionmentioning
confidence: 99%